USM EXCELS AT INNOVATE MALAYSIA DESIGN COMPETITION 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 9 August 2016 Innovate Malaysia Design Competition 2016 is one of the platforms that brings together the most ambitious, creative and smart undergraduate students in engineering or computer science, for them to work with each other in turning imagination into reality.